2014
DOI: 10.1016/j.pain.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity contributes to nociceptive sensitization in a mouse model of complex regional pain syndrome

Abstract: Complex regional pain syndrome (CRPS) is a painful, disabling, chronic condition whose etiology remains poorly understood. The recent suggestion that immunological mechanisms may underlie CRPS provides an entirely novel framework in which to study the condition and consider new approaches to treatment. Using a murine fracture/cast model of CRPS, we studied the effects of B-cell depletion using anti-CD20 antibodies or by performing experiments in genetically B-cell-deficient (µMT) mice. We observed that mice tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 66 publications
2
98
0
Order By: Relevance
“…Sera from patients with CRPS has been reported to harbor autoantibodies targeting autonomic neurons [64,65], and IgG extracted from these sera reproduce some CRPS features in mice [66]. These early passive transfer experiments suggest roles for B cells and IgM [67], and IgG autoantibodies [66]. Additionally, there is strong pathological and physiological evidence that focal injury to nerves sustained during surgery (which breaches the blood-nerve barrier) sometimes triggers autoimmune neuropathy [68].…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…Sera from patients with CRPS has been reported to harbor autoantibodies targeting autonomic neurons [64,65], and IgG extracted from these sera reproduce some CRPS features in mice [66]. These early passive transfer experiments suggest roles for B cells and IgM [67], and IgG autoantibodies [66]. Additionally, there is strong pathological and physiological evidence that focal injury to nerves sustained during surgery (which breaches the blood-nerve barrier) sometimes triggers autoimmune neuropathy [68].…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…105 Interestingly, autoimmunity has been suggested as one of the pathophysiological mechanisms that might underlie CRPS, because of the compelling evidence that CRPS is associated with an autoantibody-mediated autoimmune process in some patients 106 and in the CRPS animal model. 107 Moreover, anti-CD20 (B cell) treatment reduces IL-1 production and nociceptive responses in a laboratory model of CRPS. 107 Examination and characterization of the interactive pathways between the inflammasome and adaptive immunity leading to CRPS may provide insight into the pathophysiology and optimal treatment of CRPS.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…107 Moreover, anti-CD20 (B cell) treatment reduces IL-1 production and nociceptive responses in a laboratory model of CRPS. 107 Examination and characterization of the interactive pathways between the inflammasome and adaptive immunity leading to CRPS may provide insight into the pathophysiology and optimal treatment of CRPS.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…[16][17][18]58 Recently we observed that B cells contributed to the development and maintenance of CRPS -like changes in the mouse fracture model and postulated that IgM autoantibodies directed at antigens in the fracture limb skin and nerves contribute to nociceptive sensitization in CRPS. 23 Clinical support for this hypothesis include a recent study demonstrating that a third of CRPS patients exhibit strongly positive antinuclear antibody tests, a standard diagnostic test for autoimmune disease, 59 and small randomized trial of low dose IVIG demonstrated that some chronic CRPS patients had prolonged and dramatic symptom improvement after a single IVIG treatment 60 . Consistent with our prior results in fracture mice, at 4 weeks post-fracture in rats there was a dramatic increase in IgM and IgG deposition in the skin and sciatic nerve of the injured limb, and 4 weeks of zoledronate treatment failed to inhibit this increase (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After tibia fracture elevated levels of IgM complexes were observed in the skin and sciatic nerve of the injured limb, and fracture mice lacking B cells and immunoglobulin had attenuated post-fracture nociceptive sensitization. 23 Bisphosphonates can inhibit monocyte/ macrophage/dendritic cell migration, proliferation, and differentiation in vitro and reduce monocyte expression of TNF, IL-1, and IL-6 cytokines. [24][25][26][27][28][29] Bisphosphonate treatment also reduces serum levels of TNF, IL-1, and IL-6 in osteoporosis patients.…”
Section: Introductionmentioning
confidence: 99%